The Analysis Of Sharia Conformity To Kafalah Contract and Hasanah Card Products In Islamic Banking - Faulina Faulina; Galih Mareta Nur Ka’bah; Milna Sari; Zaitun Qamariah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study focused on assessing the conformity of sharia to kafalah contracts in Hasanah Card products. The main findings show that the implementation of kafalah contracts on Hasanah Cards still does not fully meet the required Sharia criteria. The majority of scholars are of the view that the agreement related to ujrah for kafalah services falls into the category of riba qardh, so it is forbidden. Therefore, it is important to keep the kafalah in its purity context as a form of aid and almsgiving without any element of imbalance or compensation that is not under the principles of Shariah. This research is expected to make a significant contribution to the development of Islamic financial products that are more in line with Islamic teachings. By highlighting shortcomings in the implementation of the kafalah contract in the Hasanah Card product, it is hoped that it will encourage better improvement and innovation efforts to ensure Sharia compliance in Islamic finance practices. In addition, this research is also expected to increase public awareness of the importance of applying sharia principles in every aspect of finance, to create a more transparent, fair, and under Islamic values.